Pengaruh Faktor Psikologis Terhadap Peningkatan Prestasi Atlet: Literature Review pada Studi Psikologi Olahraga - Muhammad Hikmal Akbar; Indra Yusuf; Nabile Anggoro Waskito; Putra Bangun Airlangga; Wisanggeni Akbar Priambudi (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to determine the psychological influence on athletes while analyzing psychological factors that contribute to performance improvement through a System Literature Review (SLR). The method used in this study is a qualitative method with a System Literature Review (SLR) type using a systematic article search through Publish or Perish and Google Scholar. In journals with keywords that facilitate search understanding such as: "sport psychology factors", "performance sports", "psychological factors in performance sports". The results of this study indicate that in performance sports and improving athlete performance not only focuses on physical factors, but also considers psychological factors that play an important role in improving athlete performance and achieving success. In performance sports, athletes really need motivation from many parties, including coaches, parents, teammates, and even the government, so that they can help them stay motivated and maintain focus. In addition, structured talent scouting is also needed, starting from the recruitment stage to the final coaching, so that it becomes an important basis in a psychological-based training approach for athletes.